Six Ways of Being Religious - Cannon, Dale (Open textbook library., 1996)
The book proposes the hypothesis that six generic ways of being religious may be found in any large-scale religious tradition such as Christianity or Buddhism or Islam or Hinduism: sacred rite, right action, devotion, shamanic mediation, mystical quest, and reasoned inquiry. These are recurrent ways in which, socially and individually, devout members of these traditions take up and appropriate their stories and symbols in order to draw near to, and come into right relationship with, what the traditions attest to be the ultimate reality.